Assessment of toxic potential of primary and secondary particulates/aerosols from biodiesel vis-à-vis mineral diesel fuelled engine. (May 2013) - Agarwal, Avinash Kumar; Gupta, Tarun; Dixit, Neelabh; Shukla, Pravesh Chandra
Abstract Toxicity of engine out emissions from primary and secondary aerosols has been a major cause of concern for human health and environmental impact. This study aims to evaluate comparative toxicity of nanoparticles emitted from a modern common rail direct injection engine (CRDI) fuelled with biodiesel blend (B20) vis-à-vis mineral diesel. The toxicity and potential health hazards of exhaust particles were assessed using various parameters such as nanoparticle size and number distribution, surface area distribution, elemental and organic carbon content and polycyclic aromatic hydrocarbons adsorbed onto the particle surfaces, followed by toxic equivalent factor assessment. It was found that biodiesel particulate toxicity was considerably lower in comparison to mineral diesel.